Birrul Walidain dalam Lensa Al-Qur'an: Tafsir Tematik Ayat-Ayat Berbakti kepada Orang Tua - Helmi Adam Zulfa; Agus Imam Kharomen (Al-Qadim: Jurnal Tafsir dan Ilmu Tafsir, 2025)
This study examines the concept of Birrul Walidain (devotion to parents) in depth through a thematic interpretation approach to the verses of the Qur'an. The main objective of this research is to uncover the various dimensions, urgency, and implications of the command to honor one’s parents as presented in the Holy Scripture. By comprehensively analyzing the relevant verses, this study highlights how the Qur'an places Birrul Walidain as one of the most noble acts of worship, often mentioned alongside the concept ofTawhid (monotheism). The findings indicate that the Qur'an not only commands filial devotion, but also details its forms, the ethics of interaction, and the worldly and hereafter consequences for both those who uphold it and those who neglect or violate it. This understanding is crucial for shaping the character of a pious Muslim and strengthening a harmonious social structure.